Nighttime Waking to Smoke, Stress, and Nicotine Addiction. Issue 6 (2nd November 2022) - Branstetter, Steven A.; Krebs, Nicolle M.; Muscat, Joshua E.
ABSTRACT: Introduction: Up to one-half of cigarette smokers may wake up during the night and smoke. This behavior may result in greater likelihood of cessation failure, clinically relevant sleep difficulties, and a range of health issues. Whereas the scientific literature has often attributed this behavior to nicotine dependence, up to 85% of smokers who wake at night and smoke attribute this behavior to factors other than nicotine. This study examines the relations between nicotine dependence, psychological distress, perceived stress, and waking at night to smoke. Methods: A total of 351 adult smokers from the Pennsylvania Adult Smoking Study (PASS) completed self-report surveys and provided saliva for the evaluation of cotinine values. Survey instruments included measures of nicotine addiction, perceived stress, a broad measure of global psychological distress, and a range of demographic factors. Results: Logistic regression demonstrated that nicotine addiction, psychological distress, and perceived stress were all related to waking at night to smoke, but cotinine levels were not. Mediation models found that psychological distress had a direct relation to waking at night to smoke, even when considering nicotine addiction and other causes of sleep disturbances (e.g., apnea and chronic physical pain). Alternative moderation and mediation models were conducted but did not support other plausible associations between variables. Conclusions: Waking at night to smoke is likely the result of both nicotine dependence and psychological distress. Given that cotinine levels were not associated with waking at night, the mechanisms of how nicotine dependence may affect waking at night need further investigation.